Optimization of TiO 2 nanoparticle mixed PEDOT-PSS counter electrodes for high efficiency dye sensitized solar cell - Maiaugree, Wasan; Pimanpang, Samuk; Towannang, Madsakorn; Saekow, Saman; Jarernboon, Wirat; Amornkitbamrung, Vittaya (My University, 2012)
Poly(3,4-Ethylendioxythiophene)-Poly(Styrene Sulfonate) (PEDOT-PSS) mixed with titanium dioxide (TiO 2) nanoparticles was coated on conductive glass substrate by a doctor blading method and used as dye-sensitized solar cell (DSSC) counter electrodes. The energy conversion efficiency is significantly improved after TiO 2 nanoparticle incorporation. This improvement is attributed to an increase in counter electrode catalytic activity and a decrease in counter electrode charge transfer resistance. These phenomena were observed using Cyclic Voltammetry (CV) and Electrochemical Impedance Spectroscopy (EIS), respectively. The efficiency of polymer-TiO 2 based DSSCs varied with the ratio of small (∼ 25 nm) to large (∼ 100 nm) TiO 2 nanoparticles. The highest efficiency (∼ 8.49%) was obtained with a ratio of 30% large to 70% small (wt/wt) nanoparticles inTiO 2 electrodes. This efficiency is superior to that of Pt DSSC (∼ 7.50%). © 2011 Elsevier B.V.
Keywords: Counter electrode; Dye-sensitized solar cell; PEDOT-PSS; Titanium dioxide